How People Foraging in Urban Greenspace Can Mobilize Social–Ecological Resilience During Covid-19 and Beyond - Sardeshpande, Mallika; Hurley, Patrick T.; Mollee, Eefke; Garekae, Hesekia; Dahlberg, Annika C.; Emery, Marla R.; Shackleton, Charlie (Frontiers in Sustainable Cities, 2021)
Informal foraging for food and other natural materials in urban greenspaces is an activity undertaken by many across the world. For some, foraging is a necessary means of survival and livelihood, while for others it provides cultural and recreational opportunities. In the socioeconomic crises induced by Covid-19, foraging can help communities, and especially (but not exclusively) vulnerable people, cope with the impacts of lockdowns and associated economic decline. In the long run, foraging can help improve social-ecological resilience in urban systems, particularly in response to climate, economic and disease disruptions. First, we elaborate the ways in which urban foraging can provide immediate relief from the shocks to natural, human, social, physical, and financial capital. We then describe how over time, the livelihood, food and income diversification brought about by foraging can contribute to preparedness for future uncertainties and gradual change. Cities are increasingly becoming home to the majority of humanity, and urban foraging can be one of the pathways that make cities more liveable, for humans as well as the other species we coexist with. Through the capitals framework, we explore the role foraging could play in addressing issues of biodiversity conservation, culture and education, good governance and social justice, multifunctional greenspace, and sustainable nature-based livelihoods in urban areas.